Preparation method of titanium belt for composite titanium pot

Through the preparation method of titanium strip for composite titanium pans, including hot rolling, cold rolling, annealing and electrostatic oiling processes, the problems of cold rolling strip breaking and pattern difference in the existing technology are solved, and high quality and thickness accuracy are achieved Titanium tape production meets the needs of composite rolling.

CN119259678APending Publication Date: 2025-01-07新疆湘润新材料科技有限公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411179918.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

In the production process of existing titanium tape for composite titanium pots, there are problems such as large cold rolling deformation, easy strip breakage, low material yield, large side waves and poor pattern, which is difficult to meet the needs of composite rolling.

Method used

A method for preparing titanium strips for composite titanium pans is adopted, including hot rolling of slabs, primary cold rolling, stress removal annealing, pulling, secondary cold rolling and finished product annealing, through shot blasting, pickling and electrostatic oiling and other processes, Adjust the rolling parameters and annealing temperature to improve the surface hardness and wear resistance of the titanium tape, and ensure consistency of thickness accuracy and surface quality.

Benefits of technology

It effectively solves the problem of cold-rolled strip breaking, improves the yield and production efficiency, and obtains a titanium strip for composite titanium pots with excellent shape, with high surface consistency and excellent performance, meeting the needs of composite rolling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119259678A_ABST
    Figure CN119259678A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of titanium strips, in particular to a preparation method of a titanium strip for a composite titanium pot, which comprises the following steps: S1, plate blank hot rolling: obtaining a hot-rolled titanium strip coil with the thickness of 3.0 mm; s2, primary cold rolling is conducted, specifically, a primary cold-rolled titanium coil with the thickness being 1 mm is obtained; s3, stress relief annealing is carried out; s4, secondary cold rolling is conducted, specifically, a titanium coil which is subjected to secondary cold rolling and is 0.35 mm in thickness is obtained; s5, annealing a finished product; in the production process, the strip is not prone to breakage, the titanium strip for the composite titanium pot with the excellent model can be obtained, the surface consistency of the coiled material is high, the unevenness of the obtained titanium strip is smaller than or equal to 3 mm / m, the grain size reaches the 8-10 level, and the mechanical property meets the GB / T3621-2007 standard.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of titanium strips, and in particular to a method for preparing a titanium strip for a composite titanium pot. Background Art

[0002] With the improvement of science and technology and the level of mass consumption, the concept of "titanium health" has been strongly advocated in the field of civilian titanium products. In the existing kitchen utensils, frying pans and stew pots generally use toxic Teflon coatings or slightly toxic ceramic coatings to prevent sticking. The coatings will fall off after long-term use, which will eventually harm the human body. Cookware without coatings, such as stainless steel pots, have poor non-stick properties. When used, food often sticks to the pot, affecting the taste. At the same time, heavy metals will precipitate from stainless steel after long-term use, which is harmful to human health.

[0003] Titanium and titanium alloys have many excellent physical and chemical properties, such as high specific strength, high yield strength, high fatigue limit, non-magnetic, high melting point, low expansion coefficient, good biocompatibility and corrosion resistance, etc. Therefore, from the 1950s to the 1970s, titanium was known in the industry as "air metal", "land metal" and "ocean metal". At the same time, titanium does not contain heavy metals, has antibacterial properties and good biocompatibility, and has a history of large-scale application in the field of medical implants with higher safety requirements. Therefore, titanium is a very good material choice for kitchen pots.

[0004] At present, the thickness of pure titanium coils used in composite titanium pots in the market is required to be thinner and thinner. The thickness range with a large demand is mainly wide products (990-1020mm) between 0.35 and 0.40mm. The production cost of pure titanium strips of this specification is high and difficult. Problems such as cold rolling strip breakage, poor version and performance incompatibility are prone to occur during the production process, which will seriously affect the product yield and production cost. The subsequent rolling and laminating will also cause poor rolling and insufficient bonding. The ability to stably and high-quality produce 0.35-0.40mm pure titanium strips is an urgent problem to be solved in the field of composite layered titanium strip materials.

[0005] In order to solve the above problems, the present invention decides to design a method for preparing a titanium strip for a composite titanium pot. Summary of the invention

[0006] In order to solve the above problems, the present invention provides a method for preparing a titanium strip for a composite titanium pot.

[0007] A method for preparing a titanium strip for a composite titanium pot comprises the following steps:

[0008] S1. Slab hot rolling:

[0009] A pure titanium slab is prepared, and the pure titanium slab is heated in a heating furnace, the heating temperature is 870-890° C., the holding time is 280-300 min, the start rolling temperature is 820-860° C., and then rough rolling and finish rolling are performed in sequence, the total deformation amount of rough rolling is 80-85%, the total deformation amount of finish rolling is 85-89%, the single-pass deformation amount of rough rolling and finish rolling is 20-45%, and the rolling speeds of rough rolling and finish rolling are both 3-5 m / s, to obtain a hot-rolled titanium strip coil with a thickness of 3.0 mm;

[0010] The hot-rolled titanium strip coil is shot blasted, hot continuously annealed and pickled to obtain a pickled titanium coil; wherein the hot continuous annealing temperature is 700-750° C., the travel speed is 10-15 m / min, the annealing furnace length is 100 m, and the holding time is 6-10 min;

[0011] S2, primary cold rolling:

[0012] The pickled titanium coil is subjected to a cold rolling process on a 20-roller cold rolling device, wherein the total deformation of the cold rolling process is 66-67%, the deformation of each pass is 10-15%, the rolling speed is 50-150 m / min, and the rolling force is 200-1300 KN, to obtain a cold-rolled titanium coil having a thickness of 1 mm;

[0013] S3, stress relief annealing:

[0014] Degreasing and deoiling the titanium coil after the primary cold rolling, and then performing stress relief annealing in a vacuum bell furnace by a step-by-step heating method, with a vacuum degree of 0.1-1 Pa, an annealing temperature of 570-590° C., and a holding time of 10-14 hours, and obtaining a primary annealed titanium coil after cooling in the furnace;

[0015] S4, secondary cold rolling:

[0016] The titanium coil subjected to the primary annealing is straightened to obtain a titanium coil with an unevenness of ≤8 mm / m, and then the titanium coil is subjected to secondary cold rolling on a 20-roller cold rolling device, wherein the total deformation of the secondary cold rolling is 64.5-65.5%, the deformation of each pass is 10-15%, the rolling speed is 50-150 m / min, and the rolling force is 200-1300 KN, to obtain a titanium coil after secondary cold rolling with a thickness of 0.35 mm;

[0017] S5, finished product annealing:

[0018] The titanium coil after secondary cold rolling is degreased and deoiled, and then annealed in a vacuum bell furnace by a step-by-step heating method, with a vacuum degree of 0.1-1 Pa, an annealing temperature of 570-590° C., and a holding time of 10-14 hours. After cooling in the furnace, a titanium strip for a composite titanium pot is obtained.

[0019] Furthermore, in step S1, the amount of sand for shot blasting is 700-1200 kg / min, 1.5-3.0 mm spherical cast steel sand is used, the shot blasting speed is 60-80 m / s, the spraying angle is 35-50°, and the shot blasting time is 5-7 min.

[0020] Description: Shot blasting can improve the surface roughness. Appropriate roughness is conducive to the subsequent coating adhesion. During the shot blasting process, the titanium strip surface will undergo plastic deformation and produce residual compressive stress, thereby increasing the surface hardness. Appropriate surface hardening is conducive to improving wear resistance and fatigue resistance. During the shot blasting process, the grains of the surface layer will be refined to form a nanocrystalline structure. This change in microstructure will affect the strength, plasticity and other mechanical properties of the material.

[0021] Furthermore, in step S1, the concentration ratio of the acid solution used in the pickling is: HF solution with a concentration of 18 to 24 g / L and HNO3 solution with a concentration of 160 to 240 g / L are mixed in a mass ratio of 1:2.5 to 3.5, and the acid solution temperature is 40 to 50°C.

[0022] Description: Hydrogen fluoride can effectively dissolve the oxide film and other impurities on the titanium surface, while nitric acid can dissolve pollutants on the metal surface. The combination of the two can achieve more thorough surface cleaning; during the pickling process, hydrogen fluoride and nitric acid will form a dense passivation film on the titanium surface, improving the corrosion resistance of titanium.

[0023] Furthermore, in step S1, the method for preparing the pure titanium plate is:

[0024] Using grade 1 and above titanium sponge as raw material and pressing to obtain electrode blocks, and then melting the electrode blocks twice in a vacuum consumable furnace to obtain titanium ingots: in the first melting, the vacuum degree is 0.01-0.02 Pa, the melting temperature is 1550-1650°C, the melting time is 1-1.5 hours, and the primary water-cooling circulation water pressure is 0.4-0.6 MPa; in the second melting, the vacuum degree is 0.05-0.07 Pa, the melting temperature is 1850-1950°C, the melting time is 1.5-2.5 hours, and the secondary water-cooling circulation water pressure is 0.3-0.5 MPa;

[0025] After smelting, the titanium ingot is forged, with an initial forging temperature of 850-950°C, a final forging temperature of 700-800°C, a deformation amount of 15-20% per pass, a total deformation amount of 70-90%, and a forging ratio of 3.5-4 to obtain a slab.

[0026] Note: Two vacuum melting processes can fully melt and homogenize the titanium material composition, making the final slab structure and performance more uniform; forging after two vacuum melting processes can refine the grain size of the titanium alloy and improve the mechanical properties.

[0027] Furthermore, the pressing pressure of the electrode block is 25-30 MPa, and the density of the electrode block is 3.45-3.55 g / cm 3 .

[0028] Note: Appropriate electrode block density is beneficial to heat transfer and metal flow during smelting, and helps to homogenize the composition.

[0029] Furthermore, in step S2, during the first cold rolling, the head, middle and tail of the pickled titanium coil are respectively subjected to variable roll-gap rolling by the upper and lower rollers, and the pickled titanium coil is electrostatically oiled each time the roll-gap is changed;

[0030] The head and tail portions account for 1 / 8 to 1 / 6 of the pickled titanium coil respectively, and the roll distance of the middle portion is X. The roll distance of the head portion during rolling is 1.2 to 1.3X, and the roll distance of the tail portion during rolling is 1.5 to 1.8X; wherein X is 1.1 to 1.3 times the thickness of the pickled titanium coil;

[0031] Before rolling, the pickled titanium coil at the head is electrostatically oiled with 50-60g / m 2 , voltage is 30~40kV;

[0032] When the roller pitch changes from the head to the middle, the pickled titanium coil in the middle is electrostatically oiled, and the oiling amount is 80-100g / m 2 , voltage is 70~80kV;

[0033] When the roller pitch changes from the middle to the tail, the pickled titanium coil at the tail is electrostatically oiled, with an oiling amount of 60-70g / m 2 , the voltage is 40~50kV.

[0034] Description: Zoning the roller gap and oiling amount can more finely adjust the rolling force and lubrication state of each part, thereby improving the thickness accuracy and surface quality consistency of the finished product; the head and tail of titanium materials are more prone to defects due to the instability of the coil structure or the start / stop process of the equipment. By adjusting the roller gap and optimizing the oiling of these parts, the break rate and damage risk can be reduced; the precisely controlled roller gap and oil film can improve the surface finish of the titanium coil, and electrostatic oiling can also help form a protective film to enhance the anti-corrosion performance of the finished product.

[0035] Furthermore, the lubricating oil for electrostatic oiling includes, by mass percentage, 1-2% butyl hydroxytoluene, 3-5% glycerol, 4-7% hexyldodecyl salicylic acid, 1-2% sodium vinyl silicate, 2-3% n-butyl titanate, 1-2% Mannich base, 0.5-1% succinimide, and the remainder mineral oil.

[0036] Description: Butylated hydroxytoluene, as an antioxidant, can effectively prevent the oxidation of the oil, extend the protection period of the oil film, and improve the rust resistance of titanium; ingredients such as glycerol and hexyldodecyl salicylic acid enhance the adhesion of the oil film on the surface of titanium, reduce friction, and ensure the lubrication effect during cold rolling; n-butyl titanate and sodium vinyl silicate help to form a dense protective film, reduce surface scratches, and improve the surface finish of the finished product; Mannich base and succinimide can enhance the anti-corrosion effect of the oil; the mixed use of these ingredients ensures the uniform dispersion of the oil during electrostatic spraying, avoids unevenness and accumulation of the oil film, and improves the uniformity and stability of the oiling; mineral oil, as the base oil, can adapt to the temperature changes during titanium processing and maintain the stable performance of the oil under the synergistic effect of the above additives.

[0037] Furthermore, in step S3 and step S5, the stepwise heating method is as follows: first, heating from 20-25°C to 190-210°C within 2 hours, and keeping at 190-210°C for 2 hours; then, heating from 190-210°C to 440-460°C within 2.5 hours, and keeping at 440-460°C for 4 hours; finally, heating from 440-460°C to 570-590°C within 12 hours.

[0038] Note: Direct and rapid heating will lead to a large temperature gradient inside the material, which is prone to local stress concentration and cause deformation or cracks. Step-by-step heating can alleviate this problem; and step-by-step heating can make the temperature of each part of the material more uniform, which is conducive to the homogenization of the structure and improves the performance of the material.

[0039] Compared with the existing method for preparing titanium strip for composite titanium pot, the beneficial effects of the present invention are:

[0040] (1) The existing technology for preparing titanium strip for composite titanium pots has a large cold rolling deformation, and the strip is prone to breakage in the second cold rolling process, resulting in low yield rate and production efficiency. In addition, the titanium strip for composite titanium pots has large edge waves and poor shape, which cannot meet the composite rolling requirements. The preparation method of the present application can effectively solve the above problems. The production process is not prone to strip breakage, and a titanium strip for composite titanium pots with excellent shape can be obtained, and the surface consistency of the coil is high.

[0041] (2) The preparation method of the present application adds a straightening and trimming process between the two cold rolling steps to improve the shape and edge quality and effectively avoid strip breakage during the secondary cold rolling process.

[0042] (3) The preparation method of the present application can more finely adjust the rolling force and lubrication state of each part by controlling the roll gap and oiling amount in different zones during a cold rolling, thereby improving the thickness accuracy and surface quality consistency of the finished product; the head and tail of the titanium material are more prone to defects due to the instability of the coil structure or the start / stop process of the equipment. By adjusting the roll gap and optimizing the oiling of these parts, the break rate and the risk of damage can be reduced; the precisely controlled roll gap and oil film can improve the surface finish of the titanium coil, and the electrostatic oiling can also help form a protective film to enhance the corrosion resistance of the finished product. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 is a grain structure diagram of the titanium strip head prepared in Example 1 of the present invention;

[0044] Figure 2 is a grain structure diagram of the tail of the titanium strip prepared in Example 2 of the present invention;

[0045] Figure 3 It is a comparison chart of the tensile strength results of the present invention's exploration 1;

[0046] Figure 4 It is a comparison diagram of the unevenness results of the present invention's exploration 1;

[0047] Figure 5 It is a comparison chart of the tensile strength results of the present invention's exploration 2;

[0048] Figure 6 It is a comparison diagram of the unevenness results of the present invention's exploration 2;

[0049] Figure 7 It is a comparison chart of the tensile strength results of the present invention's exploration 3;

[0050] Figure 8 It is a comparison chart of the unevenness results of the present invention's exploration 3. DETAILED DESCRIPTION

[0051] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.

[0052] Embodiment 1: A method for preparing a titanium strip for a composite titanium pot, comprising the following steps:

[0053] S1. Slab hot rolling:

[0054] Prepare a pure titanium slab, the method for preparing the pure titanium slab is:

[0055] The electrode block is obtained by pressing the sponge titanium of grade 1 or above as the raw material. The pressing pressure of the electrode block is 28 MPa and the density of the electrode block is 3.50 g / cm 3; Then, the electrode block is smelted twice in a vacuum consumable furnace to obtain a titanium ingot: in the first smelting, the vacuum degree is 0.01-0.02 Pa, the smelting temperature is 1600°C, the smelting time is 1.3 hours, and the water pressure of the first water cooling cycle is 0.5 MPa; in the second smelting, the vacuum degree is 0.06 Pa, the smelting temperature is 1900°C, the smelting time is 2 hours, and the water pressure of the second water cooling cycle is 0.4 MPa;

[0056] After smelting, the titanium ingot is forged, with an initial forging temperature of 900° C., a final forging temperature of 750° C., a deformation amount of 18% per pass, a total deformation amount of 80%, and a forging ratio of 3.8 to obtain a slab;

[0057] The slab is heated in a heating furnace at a heating temperature of 880° C., a holding time of 290 min, a start rolling temperature of 840° C., and then rough rolling and finish rolling are sequentially performed, the total deformation of the rough rolling is 82.5%, the total deformation of the finish rolling is 87%, the single-pass deformation of the rough rolling and the finish rolling is 32.5%, and the rolling speeds of the rough rolling and the finish rolling are both 4 m / s, to obtain a hot-rolled titanium strip coil with a thickness of 3.0 mm;

[0058] The hot-rolled titanium strip coil is shot blasted, hot continuously annealed and pickled to obtain a pickled titanium coil; wherein the hot continuous annealing temperature is 725°C, the travel speed is 12.5m / min, the annealing furnace length is 100m, and the holding time is 8min; the shot blasting sand amount is 950Kg / min, 2.2mm spherical cast steel sand is used, the shot blasting speed is 70m / s, the spray angle is 42°, and the shot blasting time is 6min; the acid solution concentration ratio used in the pickling is: HF solution with a concentration of 21g / L and HNO3 solution with a concentration of 200g / L are mixed in a mass ratio of 1:3, and the acid solution temperature is 45°C;

[0059] S2, primary cold rolling:

[0060] The pickled titanium coil is subjected to a cold rolling process on a 20-roller cold rolling device, wherein the total deformation of the cold rolling process is 66.5%, the deformation of each pass is 12.5%, the rolling speed is 100 m / min, the rolling force is 750 KN, and a titanium coil having a thickness of 1 mm after the cold rolling process is obtained;

[0061] S3, stress relief annealing:

[0062] Degreasing and deoiling the titanium coil after the primary cold rolling, and then performing stress relief annealing in a vacuum bell furnace by a step-by-step heating method, with a vacuum degree of 0.6 Pa, an annealing temperature of 580° C., and a holding time of 12 h, and obtaining a primary annealed titanium coil after cooling in the furnace;

[0063] S4, secondary cold rolling:

[0064] The titanium coil subjected to the primary annealing is straightened to obtain a titanium coil with an unevenness of 8 mm / m, and then the titanium coil is subjected to secondary cold rolling on a 20-roller cold rolling device, the total deformation of the secondary cold rolling is 65%, the deformation of each pass is 12.5%, the rolling speed is 100 m / min, the rolling force is 750 KN, and the titanium coil after secondary cold rolling is obtained with a thickness of 0.35 mm;

[0065] S5, finished product annealing:

[0066] The titanium coil after secondary cold rolling is degreased and deoiled, and then the finished product is annealed in a vacuum bell furnace by a step-by-step heating method, the vacuum degree is 0.6 Pa, the annealing temperature is 580° C., the insulation time is 12 hours, and the titanium strip for composite titanium pot is obtained after cooling in the furnace;

[0067] In step S3 and step S5, the stepwise heating method is: firstly, heating from 23°C to 200°C within 2 hours, and keeping at 200°C for 2 hours; then heating from 200°C to 450°C within 2.5 hours, and keeping at 450°C for 4 hours; finally, heating from 450°C to 580°C within 12 hours.

[0068] Example 2: This example is different from Example 1 in that the pressing pressure of the electrode block is 25 MPa and the density of the electrode block is 3.45 g / cm 3 .

[0069] Example 3: This example is different from Example 1 in that the pressing pressure of the electrode block is 30 MPa and the density of the electrode block is 3.55 g / cm 3 .

[0070] Example 4: This example is different from Example 1 in that, in one smelting, the vacuum degree is 0.01 Pa, the smelting temperature is 1550° C., the smelting time is 1 h, and the water pressure of the one water-cooling cycle is 0.4 MPa.

[0071] Example 5: This example is different from Example 1 in that, in one smelting, the vacuum degree is 0.02 Pa, the smelting temperature is 1650° C., the smelting time is 1.5 h, and the water pressure of the one water-cooling cycle is 0.6 MPa.

[0072] Example 6: This example is different from Example 1 in that, in the secondary smelting, the vacuum degree is 0.05 Pa, the smelting temperature is 1850°C, the smelting time is 1.5 h, and the secondary water cooling circulation water pressure is 0.3 MPa.

[0073] Example 7: This example is different from Example 1 in that, in the secondary smelting, the vacuum degree is 0.07 Pa, the smelting temperature is 1950°C, the smelting time is 2.5 h, and the secondary water cooling circulation water pressure is 0.5 MPa.

[0074] Example 8: This example is different from Example 1 in that the initial forging temperature is 950°C, the final forging temperature is 700°C, the deformation amount of each pass is 15%, the total deformation amount is 70%, and the forging ratio is 3.5.

[0075] Example 9: This example is different from Example 1 in that the initial forging temperature is 950°C, the final forging temperature is 800°C, the deformation amount of each pass is 20%, the total deformation amount is 90%, and the forging ratio is 4.

[0076] Example 10: This example is different from Example 1 in that the heating temperature is 870°C and the holding time is 280 min.

[0077] Example 11: This example is different from Example 1 in that the heating temperature is 890°C and the insulation time is 300 min.

[0078] Example 12: The difference between this example and Example 1 is that the starting rolling temperature is 820°C, the total deformation of rough rolling is 80%, the total deformation of finishing rolling is 85%, the single-pass deformation of rough rolling and finishing rolling is 20%, and the rolling speeds of rough rolling and finishing rolling are both 3m / s.

[0079] Example 13: The difference between this example and Example 1 is that the starting rolling temperature is 860°C, the total deformation of rough rolling is 85%, the total deformation of finishing rolling is 89%, the single-pass deformation of rough rolling and finishing rolling is 45%, and the rolling speeds of rough rolling and finishing rolling are both 5m / s.

[0080] Example 14: This example is different from Example 1 in that the temperature of the thermal continuous annealing is 700°C, the travel speed is 10m / min, the length of the annealing furnace is 100m, and the holding time is 6min.

[0081] Example 15: This example differs from Example 1 in that the temperature of the thermal continuous annealing is 750°C, the travel speed is 15 m / min, the length of the annealing furnace is 100 m, and the holding time is 10 min.

[0082] Example 16: The difference between this example and Example 1 is that the amount of sand used for shot blasting is 700 kg / min, 1.5 mm spherical cast steel sand is used, the shot blasting speed is 60 m / s, the spraying angle is 35°, and the shot blasting time is 5 min.

[0083] Example 17: This example is different from Example 1 in that the amount of sand used for shot blasting is 1200 kg / min, 3.0 mm spherical cast steel sand is used, the shot blasting speed is 80 m / s, the spraying angle is 50°, and the shot blasting time is 7 min.

[0084] Example 18: This example is different from Example 1 in that the acid solution used in the pickling is mixed with an HF solution having a concentration of 24 g / L and an HNO3 solution having a concentration of 160 g / L in a mass ratio of 1:2.5, and the acid solution temperature is 50°C.

[0085] Example 19: This example is different from Example 1 in that the acid solution used in the pickling is mixed with an HF solution having a concentration of 18 g / L and an HNO3 solution having a concentration of 240 g / L in a mass ratio of 1:3.5, and the acid solution temperature is 50°C.

[0086] Example 20: This example is different from Example 1 in that the total deformation of one cold rolling is 66%, the deformation of each pass is 10%, the rolling speed is 50 m / min, and the rolling force is 200 KN.

[0087] Example 21: This example differs from Example 1 in that the total deformation of one cold rolling is 67%, the deformation of each pass is 15%, the rolling speed is 150 m / min, and the rolling force is 1300 KN.

[0088] Example 22: The difference between this example and Example 1 is that in step S3, the vacuum degree is 0.1 Pa, the annealing temperature is 570°C, and the insulation time is 10 h.

[0089] Example 23: The difference between this example and Example 1 is that in step S3, the vacuum degree is 1 Pa, the annealing temperature is 590° C., and the insulation time is 14 h.

[0090] Example 24: This example differs from Example 1 in that the total deformation of the secondary cold rolling is 64.5%, the deformation of each pass is 10%, the rolling speed is 50 m / min, and the rolling force is 200 KN.

[0091] Example 25: This example is different from Example 1 in that the total deformation of the secondary cold rolling is 65.5%, the deformation of each pass is 15%, the rolling speed is 150 m / min, and the rolling force is 1300 KN.

[0092] Example 26: The difference between this example and Example 1 is that in step S5, the vacuum degree is 0.1 Pa, the annealing temperature is 570°C, and the holding time is 10 h.

[0093] Example 27: The difference between this example and Example 1 is that in step S5, the vacuum degree is 1 Pa, the annealing temperature is 590° C., and the insulation time is 14 h.

[0094] Example 28: The difference between this example and Example 1 is that in step S3 and step S5, the step-by-step heating method is: first, heating from 20°C to 210°C within 2 hours, and keeping warm at 210°C for 2 hours; then, heating from 210°C to 440°C within 2.5 hours, and keeping warm at 440°C for 4 hours; finally, heating from 440°C to 590°C within 12 hours.

[0095] Example 29: The difference between this example and Example 1 is that in step S3 and step S5, the stepwise heating method is: first, heating from 25°C to 190°C within 2 hours, and keeping at 190°C for 2 hours; then, heating from 190°C to 460°C within 2.5 hours, and keeping at 460°C for 4 hours; finally, heating from 460°C to 570°C within 12 hours.

[0096] Embodiment 30: This embodiment is different from Embodiment 1 in that, in step S2, during a cold rolling, the head, middle and tail of the pickled titanium coil are respectively subjected to variable roll-gap rolling by the upper and lower rollers, and the pickled titanium coil is electrostatically oiled each time the roll-gap is changed;

[0097] The head and tail portions each account for 1 / 7 of the pickled titanium coil, and the roll spacing of the middle portion is X. The roll spacing of the head portion during rolling is 1.25X, and the roll spacing of the tail portion during rolling is 1.65X; wherein X is 1.2 times the thickness of the pickled titanium coil;

[0098] Before rolling, the pickled titanium coil at the head is electrostatically oiled with 55g / m 2 , voltage is 35kV;

[0099] When the roller pitch changes from the head to the middle, the pickled titanium coil in the middle is electrostatically oiled, and the oiling amount is 90g / m 2 , voltage is 75kV;

[0100] When the roller pitch changes from the middle to the tail, the pickled titanium coil at the tail is electrostatically oiled, with an oiling amount of 65g / m 2 , the voltage is 45kV.

[0101] Example 31: This example differs from Example 30 in that the head and tail portions each occupy 1 / 8 of the pickled titanium coil.

[0102] Example 32: This example differs from Example 30 in that the head and tail portions each occupy 1 / 6 of the pickled titanium coil.

[0103] Example 33: The difference between this example and Example 30 is that the roll spacing of the middle part is set to X, the roll spacing during the head rolling is 1.2X, and the roll spacing during the tail rolling is 1.8X; wherein X is 1.1 times the thickness of the pickled titanium coil.

[0104] Example 34: The difference between this example and Example 30 is that the roll spacing of the middle part is set to X, the roll spacing during the head rolling is 1.3X, and the roll spacing during the tail rolling is 1.5X; wherein X is 1.3 times the thickness of the pickled titanium coil.

[0105] Example 35: This example is different from Example 30 in that the pickled titanium coil at the head is electrostatically oiled, and the oiling amount is 50g / m 2 , the voltage is 30kV.

[0106] Example 36: This example is different from Example 30 in that the pickled titanium coil at the head is electrostatically oiled, and the oiling amount is 60g / m 2 , the voltage is 40kV.

[0107] Example 37: This example is different from Example 30 in that the pickled titanium coil in the middle is electrostatically oiled, and the oiling amount is 80g / m 2 , the voltage is 70kV.

[0108] Example 38: This example is different from Example 30 in that the pickled titanium coil in the middle is electrostatically oiled, and the oiling amount is 100g / m 2 , the voltage is 80kV.

[0109] Example 39: This example is different from Example 30 in that the tail of the pickled titanium coil is electrostatically oiled, and the oiling amount is 60g / m 2 , the voltage is 40kV.

[0110] Example 40: This example is different from Example 30 in that the tail of the pickled titanium coil is electrostatically oiled, and the oiling amount is 70g / m 2 , the voltage is 50kV.

[0111] Experimental Example: The description of this experimental example is based on the scheme described in Example 1, and is intended to illustrate the practical application effect of the present invention.

[0112] Five portions of the titanium strips for the composite titanium pot prepared in each example were taken for testing of tensile strength and unevenness, and the average result of the five portions was taken as the final result, which is used as the experimental result of the titanium strip of the present application.

[0113] Table 1 Performance parameters of titanium strip in Example 1

[0114]

[0115] Combined with Table 1 Figure 1 and Figure 2 The results show that the titanium strip prepared in the present application has a large grain size, fine and uniform grains, and its mechanical properties meet the GB / T3621-2007 standard. The titanium strip has excellent performance and small unevenness.

[0116] 1. Investigate the influence of slab preparation parameters on the tensile strength and roughness of titanium strip.

[0117] Depend on Figure 3 and Figure 4 The results show that in Examples 1 to 9, the parameters of the electrode block are too small or too large, the parameters of the primary smelting are too small or too large, the parameters of the secondary smelting are too small or too large, and the forging parameters are too small or too large, which will reduce the tensile strength and unevenness of the titanium strip. In comprehensive comparison, the parameter effect of Example 1 is relatively better.

[0118] 2. Investigate the effects of hot rolling, primary cold rolling, stress relief annealing, secondary cold rolling and finished product annealing on the tensile strength and unevenness of titanium strip.

[0119] Depend on Figure 5 and Figure 6 The results show that in Examples 10 to 29, heating parameters that are too small or too large, hot rolling parameters that are too small or too large, hot continuous annealing parameters that are too small or too large, shot blasting parameters that are too small or too large, pickling parameters that are too small or too large, primary cold rolling parameters that are too small or too large, stress relief annealing parameters that are too small, secondary cold rolling parameters that are too small or too large, finished product annealing parameters that are too small, and step-type heating parameters that are too small or too large will all reduce the tensile strength and unevenness of the titanium strip. In Examples 23 and 27, the annealing parameters are larger, so that the tensile strength of the titanium strip is higher than that of Example 1, but the increase is smaller. Therefore, from an economic point of view, the parameter effect of Example 1 is relatively better.

[0120] 3. Investigate the effects of variable roll gap rolling and electrostatic oiling on the tensile strength and unevenness of titanium strip during single cold rolling.

[0121] The difference between the comparative example 1 and the embodiment 30 is that the electrostatic oiling parameters of each part are the same;

[0122] The difference between the comparative example 2 and the embodiment 30 is that the roller pitch during the tail rolling is smaller than the roller pitch during the head rolling;

[0123] Depend on Figure 7 and Figure 8The results show that the tensile strength and unevenness of Examples 30 to 40 are significantly improved compared with Example 1, so variable roll spacing rolling and electrostatic oiling provide a certain effect; in addition, due to the lack of electrostatic oiling partitions for the number of adoption and the lack of partitions for variable roll spacing in Control Example 1, the improvement is significantly reduced compared with Examples 30 to 40;

[0124] In Examples 30 to 40, the proportion of the head and tail is too small or too large, the roller spacing of the head and tail changes too small or too large, the electrostatic oiling parameters of the head are too small or too large, the electrostatic oiling parameters of the middle part are too small or too large, and the electrostatic oiling parameters of the tail are too small or too large, which will reduce the improvement in the tensile strength and unevenness of the titanium strip. Therefore, in comprehensive comparison, the parameter effect of Example 30 is relatively better.

Claims

1. A method for preparing a titanium strip for a composite titanium pot, characterized in that: The following steps are involved: S1. Slab hot rolling: A pure titanium slab is prepared, and the pure titanium slab is heated in a heating furnace, the heating temperature is 870-890° C., the holding time is 280-300 min, the start rolling temperature is 820-860° C., and then rough rolling and finish rolling are performed in sequence, the total deformation amount of rough rolling is 80-85%, the total deformation amount of finish rolling is 85-89%, the single-pass deformation amount of rough rolling and finish rolling is 20-45%, and the rolling speeds of rough rolling and finish rolling are both 3-5 m / s, to obtain a hot-rolled titanium strip coil with a thickness of 3.0 mm; The hot-rolled titanium strip coil is shot blasted, hot continuously annealed and pickled to obtain a pickled titanium coil; wherein the hot continuous annealing temperature is 700-750° C., the travel speed is 10-15 m / min, the annealing furnace length is 100 m, and the holding time is 6-10 min; S2, primary cold rolling: The pickled titanium coil is subjected to a cold rolling process on a 20-roller cold rolling device, wherein the total deformation of the cold rolling process is 66-67%, the deformation of each pass is 10-15%, the rolling speed is 50-150 m / min, and the rolling force is 200-1300 KN, to obtain a cold-rolled titanium coil having a thickness of 1 mm; S3, stress relief annealing: Degreasing and deoiling the titanium coil after the primary cold rolling, and then performing stress relief annealing in a vacuum bell furnace by a step-by-step heating method, with a vacuum degree of 0.1-1 Pa, an annealing temperature of 570-590° C., and a holding time of 10-14 hours, and obtaining a primary annealed titanium coil after cooling in the furnace; S4, secondary cold rolling: The titanium coil subjected to the primary annealing is straightened to obtain a titanium coil with an unevenness of ≤8 mm / m, and then the titanium coil is subjected to secondary cold rolling on a 20-roller cold rolling device, wherein the total deformation of the secondary cold rolling is 64.5-65.5%, the deformation of each pass is 10-15%, the rolling speed is 50-150 m / min, and the rolling force is 200-1300 KN, to obtain a titanium coil after secondary cold rolling with a thickness of 0.35 mm; S5, finished product annealing: The titanium coil after secondary cold rolling is degreased and deoiled, and then annealed in a vacuum bell furnace by a step-by-step heating method, with a vacuum degree of 0.1-1 Pa, an annealing temperature of 570-590° C., and a holding time of 10-14 hours. After cooling in the furnace, a titanium strip for a composite titanium pot is obtained.

2. The method for preparing a titanium strip for a composite titanium pot according to claim 1, characterized in that: In step S1, the amount of sand for shot blasting is 700-1200 kg / min, 1.5-3.0 mm spherical cast steel sand is used, the shot blasting speed is 60-80 m / s, the spraying angle is 35-50°, and the shot blasting time is 5-7 min.

3. The method for preparing a titanium strip for a composite titanium pot according to claim 1, characterized in that: In step S1, the concentration ratio of the acid solution used in the pickling is: HF solution with a concentration of 18-24 g / L and HNO3 solution with a concentration of 160-240 g / L are mixed in a mass ratio of 1:2.5-3.5, and the acid solution temperature is 40-50°C.

4. The method for preparing a titanium strip for a composite titanium pot according to claim 1, characterized in that: In step S1, the method for preparing the pure titanium slab is: Using grade 1 and above titanium sponge as raw material and pressing to obtain electrode blocks, and then melting the electrode blocks twice in a vacuum consumable furnace to obtain titanium ingots: in the first melting, the vacuum degree is 0.01-0.02 Pa, the melting temperature is 1550-1650°C, the melting time is 1-1.5 hours, and the primary water-cooling circulation water pressure is 0.4-0.6 MPa; in the second melting, the vacuum degree is 0.05-0.07 Pa, the melting temperature is 1850-1950°C, the melting time is 1.5-2.5 hours, and the secondary water-cooling circulation water pressure is 0.3-0.5 MPa; After smelting, the titanium ingot is forged, with an initial forging temperature of 850-950°C, a final forging temperature of 700-800°C, a deformation amount of 15-20% per pass, a total deformation amount of 70-90%, and a forging ratio of 3.5-4 to obtain a slab.

5. The method for preparing a titanium strip for a composite titanium pot according to claim 4, characterized in that: The pressing pressure of the electrode block is 25-30 MPa, and the density of the electrode block is 3.45-3.55 g / cm 3 .

6. The method for preparing a titanium strip for a composite titanium pot according to claim 1, characterized in that: In step S2, during the first cold rolling, the head, middle and tail of the pickled titanium coil are respectively subjected to variable roll-gap rolling by the upper and lower rollers, and the pickled titanium coil is electrostatically oiled each time the roll-gap is changed; The head and tail portions account for 1 / 8 to 1 / 6 of the pickled titanium coil respectively, and the roll distance of the middle portion is X. The roll distance of the head portion during rolling is 1.2 to 1.3X, and the roll distance of the tail portion during rolling is 1.5 to 1.8X; wherein X is 1.1 to 1.3 times the thickness of the pickled titanium coil; Before rolling, the pickled titanium coil at the head is electrostatically oiled with an oiling amount of 50-60g / m 2 , voltage is 30~40kV; When the roller pitch changes from the head to the middle, the pickled titanium coil in the middle is electrostatically oiled, and the oiling amount is 80-100g / m 2 , voltage is 70~80kV; When the roller pitch changes from the middle to the tail, the pickled titanium coil at the tail is electrostatically oiled, with an oiling amount of 60-70g / m 2 , the voltage is 40~50kV.

7. The method for preparing a titanium strip for a composite titanium pot according to claim 6, characterized in that: The lubricating oil for electrostatic oiling comprises, by mass percentage, 1-2% of butyl hydroxytoluene, 3-5% of glycerol, 4-7% of hexyldodecyl salicylic acid, 1-2% of vinyl sodium silicate, 2-3% of n-butyl titanate, 1-2% of Mannich base, 0.5-1% of succinimide, and the remainder of mineral oil.

8. The method for preparing a titanium strip for a composite titanium pot according to claim 1, characterized in that: In step S3 and step S5, the stepwise heating method is: firstly, heating from 20-25°C to 190-210°C within 2 hours, and keeping at 190-210°C for 2 hours, then heating from 190-210°C to 440-460°C within 2.5 hours, and keeping at 440-460°C for 4 hours; finally, heating from 440-460°C to 570-590°C within 12 hours.

Citation Information

Cited By

  • Manufacturing process of non-stick cooking container

    CN120000043A